2023
DOI: 10.1038/s41378-023-00561-9
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically actuated glaucoma drainage device for regulating intraocular pressure after implantation

Abstract: The key risk factor for glaucoma is increased intraocular pressure (IOP). Glaucoma drainage devices implanted in the eye can reduce IOP and thus stop disease progression. However, most devices currently used in clinical practice are passive and do not allow for postsurgical IOP control, which may result in serious complications such as hypotony (i.e., excessively low IOP). To enable noninvasive IOP control, we demonstrate a novel, miniature glaucoma implant that will enable the repeated adjustment of the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…In the test, 0.9 wt% saline was used as the working fluid, and a 20 μL/min flow rate was infused into the enucleated eye's anterior chamber until the system was stabilized. Notably, the used infused rate was much higher than the physiological secretion rate of the aqueous humor, to effectively balance the leakage of the aqueous humor throughout the eye and stabilize the anterior chamber, which was consistent with previous studies for ex vivo testing 13,14 of enucleated eyes. After that, the DLV was closed by manually clamping the connecting tube with a binder clip, to induce pressure buildup inside the anterior chamber and simulate an ophthalmological hypertensive condition.…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…In the test, 0.9 wt% saline was used as the working fluid, and a 20 μL/min flow rate was infused into the enucleated eye's anterior chamber until the system was stabilized. Notably, the used infused rate was much higher than the physiological secretion rate of the aqueous humor, to effectively balance the leakage of the aqueous humor throughout the eye and stabilize the anterior chamber, which was consistent with previous studies for ex vivo testing 13,14 of enucleated eyes. After that, the DLV was closed by manually clamping the connecting tube with a binder clip, to induce pressure buildup inside the anterior chamber and simulate an ophthalmological hypertensive condition.…”
Section: Methodssupporting
confidence: 86%
“…The artificial subconjunctival space‐targeting glaucoma implants are currently predominant 5,6,10,11 . Among them, passively valved subconjunctival implants remain the most accepted aqueous shunting devices, mainly due to their superior pressure management performance in reducing complications like hypotony (i.e., low IOP) when compared to the nonvalved implants, 12 in addition to the structural simplicity and higher patient compliance compared to the actively valved counterparts 13,14 . Passively valved glaucoma implants that have been used in the clinic include the Krupin and Ahmed® glaucoma valves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10g. 208,234 The micro-pencil contains homogeneously dispersed magnetic microparticles and thus its fluidic channels can be opened or closed using an externally controlled magnetic stimulus. Preliminary in vitro tests have shown that the IOP difference between the closed and open state is about 6 mmHg under a flow rate of 2.5 μL min −1 and an outlet pressure of 5 mmHg, which is sufficient to overcome hypotony.…”
Section: Microfluidics Of Minimally Invasive Glaucoma Surgery (Migs) ...mentioning
confidence: 99%